Remote ischemic preconditioning attenuates EGR-1 expression following myocardial ischemia reperfusion injury through activation of the JAK-STAT pathway. (1st February 2017) - Mudaliar, H; Rayner, B; Billah, M; Kapoor, N; Lay, W; Dona, A; Bhindi, R
Abstract: Background/objectives: Remote ischemic preconditioning (RIPC) protects the myocardium from ischemia/reperfusion (I/R) injury however the molecular pathways involved in cardioprotection are yet to be fully delineated. Transcription factor Early growth response-1 (Egr-1) is a key upstream activator in a variety of cardiovascular diseases. In this study, we elucidated the role of RIPC in modulating the regulation of Egr-1. Methods: This study subjected rats to transient blockade of the left anterior descending (LAD) coronary artery with or without prior RIPC of the hind-limb muscle and thereafter excised the heart 24 h following surgical intervention. In vitro, rat cardiac myoblast H9c2 cells were exposed to ischemic preconditioning by subjecting them to 3 cycles of alternating nitrogen-flushed hypoxia and normoxia. These preconditioned media were added to recipient H9c2 cells which were then subjected to 30 min of hypoxia followed by 30 min of normoxia to simulate myocardial I/R injury. Thereafter, the effects of RIPC on cell viability, apoptosis and inflammatory markers were assessed. Results: We showed reduced infarct size and suppressed Egr-1 in the heart of rats when RIPC was administered to the hind leg. In vitro, we showed that RIPC improved cell viability, reduced apoptosis and attenuated Egr-1 in recipient cells. Conclusions: Selective inhibition of intracellular signaling pathways confirmed that RIPC increased production of intracellular nitric oxide (NO) and reactive oxygen species (ROS) via activation of the JAK-STAT pathway which then inactivated I/R-induced ERK 1/2 signaling pathways, ultimately leading to the suppression of Egr-1.